2014
DOI: 10.1128/aac.02346-13
|View full text |Cite
|
Sign up to set email alerts
|

Role of Acinetobacter baumannii UmuD Homologs in Antibiotic Resistance Acquired through DNA Damage-Induced Mutagenesis

Abstract: cThe role of Acinetobacter baumannii ATCC 17978 UmuDC homologs A1S_0636-A1S_0637, A1S_1174-A1S_1173, and A1S_1389 (UmuD Ab ) in antibiotic resistance acquired through UV-induced mutagenesis was evaluated. Neither the growth rate nor the UV-related survival of any of the three mutants was significantly different from that of the wild-type parental strain. However, all mutants, and especially the umuD Ab mutant, were less able to acquire resistance to rifampin and streptomycin through the activities of their err… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…As shown in Fig. 2, there was a clear correlation between the increased expression of several umuDC genes and the increase in mutagenesis, which might be explained by the direct action of the errorprone DNA polymerase V (encoded by the umuDC genes) in the generation of antibiotic resistance, including to rifampin, as we recently demonstrated (7). Specifically, mutagenesis increased significantly after the treatment of A. baumannii cultures with the MC2h of either ciprofloxacin or tetracycline (P Ͻ 0.01), whereas the induction of mutagenesis was not augmented in response to the MC2h of either meropenem or colistin (Fig.…”
mentioning
confidence: 95%
See 3 more Smart Citations
“…As shown in Fig. 2, there was a clear correlation between the increased expression of several umuDC genes and the increase in mutagenesis, which might be explained by the direct action of the errorprone DNA polymerase V (encoded by the umuDC genes) in the generation of antibiotic resistance, including to rifampin, as we recently demonstrated (7). Specifically, mutagenesis increased significantly after the treatment of A. baumannii cultures with the MC2h of either ciprofloxacin or tetracycline (P Ͻ 0.01), whereas the induction of mutagenesis was not augmented in response to the MC2h of either meropenem or colistin (Fig.…”
mentioning
confidence: 95%
“…baumannii contains multiple umuDC operons and unlinked umuC and umuD genes, all of which encode components of errorprone DNA polymerase V (6). In A. baumannii strain ATCC 17978, the induction of these components after DNA damage leads to the introduction of point mutations in the bacterial genome, including those able to generate antibiotic resistance (7,8). Previous studies showed that the umuD and umuC genes of A. baumannii are induced by ciprofloxacin, which is also a strong inducer of the SOS response (6).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…As in other bacteria, A. baumannii achieves resistance against certain antimicrobials through single mutations in the corresponding target genes (i.e., point mutations in the rpoB gene can generate resistance to rifampin [2]). In previous works, we demonstrated that this bacterium contains multiple components of error-prone DNA polymerases, whose induction after DNA damage leads to the introduction of point mutations in the bacterial genome, including those conferring antibiotic resistance (3,4).…”
mentioning
confidence: 99%